The Book of Leviticus Interpreted as Jewish Community - Harris, Robert A. (Studies in Christian-Jewish Relations, 2011)
This article addresses an essay, published in 2001 by John Van Engen, entitled "Ralph of Flaix: The Book of Leviticus Interpreted as Christian Community.” Ralph’s voluminous commentary, composed and published in the mid-twelfth century, aimed, in Van Engen’s words, at “refuting Jewish arguments” about the biblical book and the nature of the levitical law, particularly as these arguments might influence young Christian clerics who were “fascinated and troubled by a close reading of the biblical text.” The present article examines three rabbinic commentaries on Leviticus roughly contemporary with Ralph, those of Rashi, Rashbam and R. Joseph Bekhor Shor. Through examining the “close reading” through which these three exegetes interpreted specific biblical texts, the article considers whether or not they presented what might be considered as “the Book of Leviticus Interpreted as Jewish Community” and as such conveyed what may have been the types of arguments with which Ralph was in conversation. The article does not attempt to provide a direct correspondence between specific Jewish and Christian exegetes. Rather, the article suggests that the content and form of 12th century Jewish and Christian biblical exegesis bespeak a type of conversation among those using the literary genre of “commentary writing,” and that it is possible to gain an understanding of the contours of that conversation through analysis of the commentaries they wrote. Additionally, the article examines ways in which medieval Jewish exegetes may have advanced arguments in their commentaries that were intended to sustain the Jewish community in their observances and belief structures in the presence of Christian hegemony.